Nyaman ehs... Restaurant / Doris Mala Aun … [et.al.]. - Aun, Doris Mala; William, Landan; Madhi, Faizal; Sa'id, Rozaidah; Amin, Rashidah (2007)
After doing extensive research on the business opportunity available in Satok, our group decided to specify our business in selling our food. Our group has come up with the business plan of partnership whereby our organization's name will be known as Nyaman Ehs Restaurant. The General Manager is the head of the business company. This position is responsible for all management for his company that includes employees' welfare. The entire decision making is in his hand after discussion with the Board of Director. He also leading, controlling, planning and looking for the business opportunities. He wills assisted by other four shareholders that have been agree to cooperate with him to establish the Nyaman Ehs Restaurant.